Developing English reading and writing materials for Automotive Engineering program in vocational high school - Endang Lestari; Joko Priyana (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2020)
The aims of this study are: (1) to identify the needs of grade 11 students of the Automotive Engineering Study Program in learning reading and writing, and (2) to develop appropriate English reading and writing learning materials. This is research and development that employed Jolly and Bolitho's model with some adaptation. The development procedure consists of conducting needs analysis, designing the syllabus, developing learning materials, expert judgment, conducting field testing, and materials evaluation. The research subject was 64 grade XI students of Light Vehicle Engineering or Teknik Kendaraan Ringan (TKR) at Vocational High School (VHS) AX. The needs analysis data indicate that, in learning reading, the students want to learn simple instructions and vocabulary items relevant to the automotive field. They also want to learn to write letters and create simple reports that are relevant to the automotive field. Regarding the theoretical validation, the appropriateness of learning materials is categorized as